Illegal Fishing in the Natuna Sea: How UNCLOS 1982 Shapes Law Enforcement Between Vietnam and Indonesia - Scoornova, Purnandya Arya Aji; Lubis, Muhammad Ikhsan; Qoiri, Mutmainah Nur; Ahmad, Nurul Hidayah Binte; Yifan, Liu; O’Connor, Liam James (Universitas Negeri Semarang, 2024)
Illegal, unreported, and unregulated (IUU) fishing poses a significant threat to marine ecosystems, coastal livelihoods, and regional security, particularly in the strategically important Natuna Sea. This paper examines how the United Nations Convention on the Law of the Sea (UNCLOS) 1982 provides the legal framework for addressing illegal fishing activities and shaping law enforcement strategies between Vietnam and Indonesia. The study analyzes the obligations of coastal and flag states under UNCLOS, focusing on exclusive economic zones (EEZs), sovereign rights over marine resources, and the responsibilities to prevent, deter, and penalize IUU fishing. Through a case study approach, the article explores specific incidents involving Vietnamese fishing vessels operating in Indonesia’s EEZ around the Natuna Sea. It assesses how Indonesia has leveraged UNCLOS provisions, alongside domestic maritime law, to assert sovereignty, enforce regulations, and protect marine resources. The study also highlights challenges in enforcement, including jurisdictional ambiguities, resource constraints, and diplomatic tensions that complicate bilateral and regional responses. The analysis demonstrates that while UNCLOS 1982 establishes clear legal standards for maritime governance, its effectiveness depends on coordinated law enforcement, regional cooperation, and the integration of domestic and international legal mechanisms. The paper argues that addressing illegal fishing in the Natuna Sea requires not only adherence to UNCLOS but also proactive diplomatic engagement, capacity-building, and multilateral cooperation within Southeast Asia. Ultimately, the study concludes that UNCLOS serves as both a legal foundation and a practical tool for promoting sustainable fisheries management, strengthening maritime security, and mitigating conflict between Vietnam and Indonesia in the Natuna Sea.